2022
DOI: 10.1186/s13054-022-03896-3
|View full text |Cite
|
Sign up to set email alerts
|

Omega-6 sparing effects of parenteral lipid emulsions—an updated systematic review and meta-analysis on clinical outcomes in critically ill patients

Abstract: Background Parenteral lipid emulsions in critical care are traditionally based on soybean oil (SO) and rich in pro-inflammatory omega-6 fatty acids (FAs). Parenteral nutrition (PN) strategies with the aim of reducing omega-6 FAs may potentially decrease the morbidity and mortality in critically ill patients. Methods A systematic search of MEDLINE, EMBASE, CINAHL and CENTRAL was conducted to identify all randomized controlled trials in critically il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
33
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 81 publications
(48 reference statements)
4
33
0
1
Order By: Relevance
“…The result agreed with the meta-analysis of Lu et al [ 25 ], which found shorter ventilation days in patients with sepsis receiving omega-3 supplementation. In addition, it was recently found that both the standard administration of fish oil alone and fish-oil-containing parenteral nutrition had a clinical benefit on overall mortality, 28-day mortality, morbidity, length of ICU stay, and infectious complications in critically ill patients [ 26 ]. It is also interesting to note that the presence of mechanical ventilation could predict the risk of mortality in burn patients [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The result agreed with the meta-analysis of Lu et al [ 25 ], which found shorter ventilation days in patients with sepsis receiving omega-3 supplementation. In addition, it was recently found that both the standard administration of fish oil alone and fish-oil-containing parenteral nutrition had a clinical benefit on overall mortality, 28-day mortality, morbidity, length of ICU stay, and infectious complications in critically ill patients [ 26 ]. It is also interesting to note that the presence of mechanical ventilation could predict the risk of mortality in burn patients [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…This scoring system ranges from 0 to 14 points (higher score indicates higher study quality). This quality assessment tool has been used in prior critical care nutrition systematic reviews and allows for comparisons of quality across topics and across time [16][17][18]. A third author resolved any disagreement.…”
Section: Study Quality and Risk Of Bias Assessmentmentioning
confidence: 99%
“…In the following section, we compare studies in our metaanalysis of fish oil-containing ILE to the recent systematic review and meta-analysis by Notz and colleagues. 8…”
Section: The Authors Imply the European Society For Clinical Nutritio...mentioning
confidence: 99%